Slow Cooling of High‐Energy C Excitons Is Limited by Intervalley‐Transfer in Monolayer MoS 2 - Li, Yuanzheng; Shi, Jia; Chen, Heyu; Mi, Yang; Du, Wenna; Sui, Xinyu; Jiang, Chuanxiu; Liu, Weizhen; Xu, Haiyang; Liu, Xinfeng (Laser & photonics reviews, 2019)
High‐energy C exciton in 2D transition metal dichalcogenides with strong photon absorption can be utilized prospectively in light‐harvesting and opto‐electric devices. Here, a detailed study on C exciton dynamics in monolayer MoS 2 is presented by femtosecond transient absorption (TA) spectroscopy. In the experiment, the C exciton with unique parallel band structure exhibits a slow process within tens of picoseconds (≈10–50 ps) as well as a fast process within several picoseconds (≈1–6 ps) instead of previous reported ultrafast cooling (<500 fs) process. From TA spectroscopy, the experimental results confirmed that the relatively slow cooling of C exciton is mainly limited by the rates of intervalley transfer rather than Pauli blocking effect from band‐edge excitons. The timescale of intervalley transfer is longer than that of intraband relaxation of C exciton, therefore, leading to the slow cooling of C exciton. Moreover, intervalley transfer time are estimated with two processes of 5.1 ± 0.6 ps and 69.5 ± 8 ps when the pump fluence is ≈127 µJ cm −2 . This work provides further understanding of the ultrafast dynamics of C exciton in monolayer MoS 2 and opens new opportunities for opto‐electric related applications.